2022
DOI: 10.1053/j.gastro.2021.08.041
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet Promotes Colorectal Tumorigenesis Through Modulating Gut Microbiota and Metabolites

Abstract: See Covering the Cover synopsis on page 2; See editorial on page 38.BACKGROUND AND AIMS: Dietary fat intake is associated with increased risk of colorectal cancer (CRC). We examined the role of high-fat diet (HFD) in driving CRC through modulating gut microbiota and metabolites. METHODS: HFD or control diet was fed to mice littermates in CRC mouse models of an azoxymethane (AOM) model and Apc min/þ model, with or without antibiotics cocktail treatment. Germ-free mice for fecal microbiota transplantation were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
152
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(184 citation statements)
references
References 40 publications
4
152
0
Order By: Relevance
“…Accordingly, regulating the immune imbalance of Thl7/Treg cells and inducing the reconstruction of immune tolerance may become a potential treatment modality for autoimmune diseases, such as MG. Studies have revealed that environmental factors, especially dietary factors, can alter the gut microbiota composition and its metabolic activity , which produce adverse implications for human health ( 31 ). For instance, alterations in the gut microbiota caused by a Western high-fat diet have recently been recognized as a major contributing factor to the colorectal cancer epidemic ( 32 ) . High -sucrose- high - fat dietary patterns were supposed to participate in the asthma pathogenesis through intestinal bacteria ( 33 , 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, regulating the immune imbalance of Thl7/Treg cells and inducing the reconstruction of immune tolerance may become a potential treatment modality for autoimmune diseases, such as MG. Studies have revealed that environmental factors, especially dietary factors, can alter the gut microbiota composition and its metabolic activity , which produce adverse implications for human health ( 31 ). For instance, alterations in the gut microbiota caused by a Western high-fat diet have recently been recognized as a major contributing factor to the colorectal cancer epidemic ( 32 ) . High -sucrose- high - fat dietary patterns were supposed to participate in the asthma pathogenesis through intestinal bacteria ( 33 , 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, as pointed by a recent analysis of the relation between dietary factors and the microbiome of healthy volunteers and IBD patients, processed and animal foods are associated with increased abundances of Firmicutes and Ruminococcus species, but plant foods and fish positively influence SCFA-producing commensals and restrain pathobionts, diet thereby influencing a characteristic microbial environment of intestinal inflammation [114]. Furthermore, high-fat diet also drives colorectal tumorigenesis in mice via intestinal dysbiosis, metabolite dysregulation and gut barrier dysfunction [115].…”
Section: Dietary Compounds and The Mucus Layer In Ibdmentioning
confidence: 99%
“…Antigen-specific activation of T and B cells imparts the immunological memory to the existing microbiome. their microbial communities have more disease (Yang et al, 2021). Further, the combined effects of the host response and bacteria on intestinal inflammation and CRC were illustrated in a study showing that inoculation of Rag-2-deficient mice with H. hepaticus induced inflammation and colonic tumors (Erdman and Poutahidis, 2017).…”
Section: Contribution Of the Microbiota To Crcmentioning
confidence: 99%
“…The gut microbiome evolves and diversifies throughout life depending on the type of birth, diet, lifestyle, geographic factors and medications ( Fiorentini et al., 2020 ; Dixit et al., 2021 ). The impact of diet and the microbiota on CRC is evidenced by data showing that mice fed a high fat diet leading to changes in their microbial communities have more disease ( Yang et al., 2021 ). Further, the combined effects of the host response and bacteria on intestinal inflammation and CRC were illustrated in a study showing that inoculation of Rag-2-deficient mice with H. hepaticus induced inflammation and colonic tumors ( Erdman and Poutahidis, 2017 ).…”
Section: Contribution Of the Microbiota To Crcmentioning
confidence: 99%